We have to find the values of x for which the following inequation holds : 3x - 6 < 2x + 4
3x - 6 < 2x + 4
subtract 2x from both the sides
=> 3x - 2x - 6 < 2x - 2x + 4
=> x - 6 < 4
add 6 to both the sides
=> x - 6 + 6 < 4 + 6
=> x < 10
Therefore x < 10.
To solve the inequality 3x-6<2x+4.
We subtract 2x from both sides of the inequality 2x-6< 2x+4:
=> x-6 < 4.
We add 6 to both sides:
x < 4+6 = 10.
Therefore 3x-6< 2x+4 gives us the solutuion x < 10.
To find the equivalent means to determine the range of values of x that makes the inequality to hold.
We'll solve the inequality separating x to the left side.We'll add 6 both sides and we'll subtract 2x both sides:
3x - 2x < 6 + 4
We'll combine like terms:
x < 10
The interval of admissible values of x is (-infinite , 10).
The equivalent of the given inequality is x < 10.